Targeting Mitochondrial Singlet Oxygen Dynamics Offers New Perspectives for Effective Metabolic Therapies of Cancer - da Veiga Moreira, Jorgelindo; Schwartz, Laurent; Jolicoeur, Mario (Frontiers in Oncology, 2020)
The occurrence of mitochondrial respiration has allowed evolution toward more complex and advanced life forms. However, its dysfunction is now also seen as the most probable cause of one of the biggest scourges in human health, cancer. Conventional cancer treatments such as chemotherapy, which mainly focus on disrupting the cell division process, have shown being effective in the attenuation of various cancers but also showing significant limits as well as serious sides effects. Indeed, the idea that cancer is a metabolic disease with mitochondria as the central site of the pathology is now emerging, and we provide here a review supporting this “novel” hypothesis re-actualizing past century Otto Warburg's thoughts. Our conclusion, while integrating literature, is that mitochondrial activity and, in particular, the activity of cytochrome c oxidase, complex IV of the ETC, plays a fundamental role in the effectiveness or non-effectiveness of chemotherapy, immunotherapy and probably radiotherapy treatments. We therefore propose that cancer cells mitochondrial singlet oxygen (1O2) dynamics may be an efficient target for metabolic therapy development.